Efficiency of Cardiotropic Therapy in Neonatal Infants with Posthypoxic Myocardial Damage - Yu. N. Belova; A. A. Tarasova; I. F. Ostreikov (Общая реаниматология)
Objective: to define the optimal tranexamic acid dosage regimen to reduce perioperative blood loss during total endo-prosthetic hip joint replacement (TEHJR). Subjects and methods. A randomized controlled trial enrolled 90 patients admitted for elective primary cementless TEHJR. Prior to surgery, all the patients were given an intravenous bolus injection of tranexamic acid in a dose of 1 g. A day before surgery, the patients were divided into 3 groups of 30 subjects each. In Group 1, tranexamic acid was administered only before incision of the skin. In Group 2, a second bolus of tranexamic acid 1 g was injected 3 hours after start of surgery. In Group 3, 1 g of tranexamic acid was readminis-tered 6 hours following surgery if drainage blood loss volume exceeded 200 ml. Results. No statistically significant differences were found between the study patient groups in terms of the amount of blood loss, the blood levels of hemoglobin, needs for hemotransfusion therapy, and the frequency of postoperative complications. Conclusion. A second bolus of tranexamic acid 1 g does not reduce the amount of blood loss as compared to a single preoperative bolus dose of tranexamic acid 1 g during elective primary cementless TEHJP. Key words: tranexamic acid, endoprosthetic hip joint replacement, blood loss.